Anthropological Engagement in the International Sphere: A Conversation Grounded in Swiss Experiences - Larsen, Peter; Bleeker, Mô; Hertz, Ellen; Käser, Isabel; Leemann, Esther; Mossman Riva, Susan; Schapira, Raphael; Schulz, Yvan (Swiss Journal of Sociocultural Anthropology, 2022)
As anthropologists increasingly embark upon the study of the international sphere, this often builds on different forms of engagement within and around organizations, processes, and institutional corridors. The co-authors, building upon a round table exchange, address the advantages and dilemmas of anthropological engagement in the field of international governance, including humanitarian work, diplomacy, international organizations, the Swiss federal government, NGOs, and multinationals.